Aula invertida no ensino de processos educativos em saúde: experiência pedagógica na perspectiva de estudantes de enfermagem - SANTOS, Bárbara Coelho dos (2020)
The study aims to reveal the perception of undergraduate nursing students about the use of inverted classroom methods in the teaching of health education processes, since this pedagogical model can contribute to teaching in the area when considering the need to train Critical-reflexive and creative professionals and based theoretically in the field of Health education. This is a descriptive study with a qualitative approach, developed with twelve nursing undergraduate students from a public university in the north of the country. The data collection was developed through an individual interview with semi-structured questions. To analyze the data, Strauss; Corbin (2008) Data Based Theory (TFD) technique was used. For the analytical process it was necessary to conceptualize, separate and interconnect the data among each other through the open and axial coding phases, developed with the aid of the trial version of the Atlas TI® program. A total of six categories emerged from the data analysis, namely: Student learning process; Understanding about inverted classroom; The development of content "pedagogical conceptions" from the Just in Time Teaching method; The development of the content "education in the educational process in health" from the Peer Instruction method; Difficulties and challenges of the teaching-learning process; Evaluations and suggestions about the teaching-learning process. The results showed that the research was satisfactory in elucidating students' main perceptions about the use of the inverted class. It was noticed that because it is a pedagogical model different from the usual approaches, in general the students demonstrate the need to experience more experiences with the inverted class, which can influence directly in the learning process of the same, as well as in their performance throughout the training. It was identified that the students developed abilities regarding the correct conceptualization of the subjects discussed, but not all reached a critical-reflective view about them, which can be due to the fragile accountability before the previous study and the own neglect of the discipline, which is still seen, by some students as less important to the others.